ANALYSIS OF ACCOUNTABILITY AND TRANSPARENCY IN THE MANAGEMENT OF SCHOOL OPERATIONAL ASSISTANCE (BOS) FUNDS AT SDK 037 NANGA - Septiyani Mehan, Kornelia; Herdi, Henrikus; Yanitza Salvanos, Yan (Program Studi Akuntansi Fakultas Ekonomi dan BisnisUniversitas Nusa Nipa, 2024)
Accountability and transparency are essential policies in school financial management that must be implemented effectively. The accountability and transparency of BOS fund management are crucial as their implementation can foster trust in the school and enhance the participation of school stakeholders. To achieve school objectives, school need to adopt better financial management practices, including the application of the principles of accountability and transparency in BOS fund management. The objectives of this rescarch are: (1) to understand the principles of accountability in the management of school operational assistance funds at SDK 037 Nanga, and (2) to assess the implementation of transparency principles in the management of these funds. The researcher was conducted at SDK 037 Nanga, utilizing a descriptive qualitative analysis method. Data were collected through observation, interviews, and documentation. The researcher interviewed several key informants, including the principal, the school treasurer, and the head of the school committee. The results indicate that the principles of accountability and transparency are being implemented effectively, evidenced by the existence of an RKAS (School Budget and Activity Plan) as a planning tool for BOS funds, the alignment between fund usage and the technical guidelines, as well as open reporting and accountability to the school and government. These findings show that the school has adhered to the principles of accountability and transparency in the management of BOS funds following government regulations and the technical guidelines for BOS fund usage.